2021
DOI: 10.1111/joss.12704
|View full text |Cite
|
Sign up to set email alerts
|

Sensory properties and consumer acceptance of ready‐to‐drink vanilla protein beverages

Abstract: Ready-to-drink (RTD) protein beverages are growing in popularity in the US market.Protein beverages vary in protein amount and source and as such, have substantially different sensory experiences. This study applied descriptive analysis and consumer acceptance testing to identify sensory properties and drivers of like and dislike in vanilla RTD protein beverages. A category survey with 33 beverages were conducted by a trained panel. Ten representative beverages were evaluated by vanilla protein beverage consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Previous studies have found that CATA questionnaires provide reproducible results, as well as consistency among descriptions of the sensory attributes of food (Ares et al, 2013; Dooley, Lee, & Meullenet, 2010; Jaeger et al, 2013). The CATA questionnaire is an efficient method, as it requires minimal instruction to the panelists, is reasonably easy to understand (Dooley et al, 2010), and it can discriminate the sensory attributes in many complex products (da Silva, Peano, & Giuggioli, 2021; de Melo, de Dutra, & Alencar, 2021; Foguel, Ract, & da Silva, 2021; Liu, Toro‐Gipson, & Drake, 2021; Rodrigues et al, 2021). For this reason, this method has been widely used to evaluate the sensory attributes of wine (Brand, Panzeri, & Buica, 2020; Puyares, Ares, & Carrau, 2010; Rinaldi, Vecchio, & Moio, 2021; Schumaker, Diako, Castura, Edwards, & Ross, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that CATA questionnaires provide reproducible results, as well as consistency among descriptions of the sensory attributes of food (Ares et al, 2013; Dooley, Lee, & Meullenet, 2010; Jaeger et al, 2013). The CATA questionnaire is an efficient method, as it requires minimal instruction to the panelists, is reasonably easy to understand (Dooley et al, 2010), and it can discriminate the sensory attributes in many complex products (da Silva, Peano, & Giuggioli, 2021; de Melo, de Dutra, & Alencar, 2021; Foguel, Ract, & da Silva, 2021; Liu, Toro‐Gipson, & Drake, 2021; Rodrigues et al, 2021). For this reason, this method has been widely used to evaluate the sensory attributes of wine (Brand, Panzeri, & Buica, 2020; Puyares, Ares, & Carrau, 2010; Rinaldi, Vecchio, & Moio, 2021; Schumaker, Diako, Castura, Edwards, & Ross, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Seven commercial ready‐to‐drink (RTD) vanilla‐flavored protein beverages (Table 2) with a variety of different sweeteners, sweet taste intensities, protein sources, and protein loads were selected for TCATA and TR analysis. Beverages (Figure 1a,b) were selected from a set of 33 commercial protein beverages that were evaluated in a previous study (Liu et al, 2021). The RTD beverages were selected to give high differentiation between beverages based on sensory profile means and the first four components in principal component analysis (PCA; see PCA biplots; Figure 1a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Principal component analysis biplot of the sensory (trained panel) properties of 33 commercial vanilla ready‐to‐drink protein beverages—(a) F1 and F2; (b) F3 and F4 (used with permission from Liu et al, 2021). Beverages with bold box were selected for the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations